Development of e-modules based on science literacy and Islamic values in ecosystem materials - Achmad Ali Fikri; Alfiyatul Rahmaniyyah (Universitas Muhammadiyah Malang, 2023)
In the reality of general education, many teachers still use conventional teaching materials, namely teaching materials that are ready, can be purchased instantly, without having to plan, prepare and organize themselves. The purpose of this study was to determine the feasibility of developing e-modules based on scientific literacy and Islamic value in biology learning on ecosystem material for class X IPA at MA Mu'allimat NU Kudus. This Study use he 4-D research model which was modified into a 3-D development model by eliminating the disseminate stage so that the research was only carried out until the develop stage. The subjects of the product trial totaling 42 students. Data collection techniques with validation instruments by material expert lecturers, media expert lecturers, practitioners, and the student response questionnaire. The results of the material expert validation were obtained